The Effect of Various Concentration BAP (6-Benzyl Amino Purine) on Orchid Growth (Macodes petola (Blume) Lindl.) In-Vitro - Muchsin, Muchfa Eprilia; Supriatna, Ateng; Adawiyah, Ayuni; Darniwa, Adisty Virakawugi (BERKALA SAINSTEK, 2022)
Macodes petola (Blume) Lindl. has an attractive of leaves veins motif with letters pattern, so it has a high economic value. Tissue culture technique is reported as the best way of plant propagation in short time. BAP (6-Benzyl Amino Purine) has a role in stimulating shoot growth with a certain concentration. The purpose of this study was to determine the effect of Various Concentration BAP (6-Benzyl Amino Purine) on Orchid Growth (M petola (Blume) Lindl.) in vitro. This study used a completely randomized design (CRD) with 4 concentration BAP levels (0; 0.5; 1; 1.5 ppm) with 3 replication. Based on the results of the study, it showed that up to 60 DAP (Day After Planting) the composition of the media with a concentration of 0 ppm BAP had a higher average value for the increase in the stem height, number of shoots and number of roots, namely 1.77±0.798 cm, 2.4 ± 1,528 shoot and 2.4 ± 2,082 root. In contrast to the concentration of 1.5 ppm at this concentration it has a low average value the parameters of stem height, number of shoots and number of roots.